Managing organizations in the creative economy organizational behaviour for the cultural sector - Saintilan, Paul; Schreiber, David 1975- (Discovering the creative industries, 2023)
"The creative and cultural industries represent a growing and important sector in the global economy. Thriving in these industries is particularly tough and organizations face unique challenges in the digital age. This textbook provides a vivid initiation into the creative industries workplace. Managing Organizations in the Creative Economy is the first textbook of its kind, introducing organizational behaviour theories and applying them to the creative world. The text is underpinned by the latest research and theoretical insights into creative industries management and organizational behaviour, covering key topics such as structure, culture and the management of change and creativity as well as contemporary issues such as diversity, sustainability, managing stress, wellbeing and self-care, and remote working. The authors bring theory to life through practical examples and cases provided by industry experts, supported by specially created companion videos featuring managerial responses to the cases. This second edition textbook provides readers with an updated applied theoretical understanding of organizational behaviour that will be of particular benefit to those looking to work in the creative and cultural industries. Students on courses such as arts business, arts management and music business, and even students within the broader study of the entertainment and creative industries, will find this to be a vital read"--Provided by publisher.